Penerapan Agroteknologi Konservasi dalam Usahatani Kentang di Desa Kebun Baru, Kecamatan Kayu Aro Barat, Kabupaten Kerinci - Henny H.; Neliyati Neliyati; Zulkarnain Zulkarnain; Sunarti Sunarti (Buletin Dharmas Andalas, 2026)
Vegetable farming in Kayu Aro Barat District is generally on sloping land with Andisol soil which is sensitive to erosion and high P retention by amorphous minerals and Al-humus. However, farmers plant potatoes as the main commodity with ridges along the slope, excessive chemical fertilizers, especially P, and without adequate organic fertilizers with relatively low productivity. Community service activities in partnership with the G7 Farmers Group and the Arimbi Women's Farmers Group in Kebun Baru Village introduced "Conservation Agrotechnology (CA)" in the form of crop ridges cutting the slope, 1 ton of Dolomite, 10 tons of chicken manure and 300-350 kg of SP-36 per hectare. The activity began with a discussion of problems and solutions. The application of AK with the Demonstration Plot Method, namely planting 225 kg of quality potato seeds on +1000 m2/demonstration plot, directly by farmers on the land of each group. Both farmer groups played an active and very enthusiastic role in every stage until harvest. The harvest exceeded farmers' expectations, with potato yields very satisfactory (2,655 kg and 2,474 kg in each demonstration plot, averaging 25.65 tons/ha) and excellent quality. Farmers were very satisfied and motivated to implement and develop the AK, which is expected to foster a "conservation-based vegetable farming" in Kebun Baru Village in particular, and Kayu Aro Barat District in general.